Markaðssetning á tónlist í nútímasamfélagi : hvernig getur sjálfstætt starfandi tónlistarfólk markaðssett sig sem best í tónlistarumhverfi samtímans? - Árni Freyr Jónsson 1991- (2019)
Through a method of interviews and researching existing studies in marketing this project aims to identify the most important steps for upcoming independent musical artists to take in order to successfully gain an audience. By personal experience and through both formal and informal interviews with musicians and music agents in the Reykjavík area, and by researching pre-existing articles on the subject the author identified a lack of interest shown by a large number of independent musicians in exploring and learning ways to brand and market their music. The aim of the project was to locate and sum up these ways and lay them out in a step-by-step format. The conclusion of these studies is that although a combination of many things, the creation of a clear and concise brand is the best way for an upcoming musical artist to get an early foothold and quickly gain attention in today‘s fast moving market.